2014
DOI: 10.1179/2045772314y.0000000224
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis, a novel type of programmed cell death, contributes to early neural cells damage after spinal cord injury in adult mice

Abstract: Necroptosis contributes to necroptotic cell death and influences functional outcome after SCI in adult mice. The inhibition of necroptosis by necrostatin-1 may have therapeutic potential for patients with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 29 publications
(43 reference statements)
3
74
0
Order By: Relevance
“…However, emerging evidence has shown that necrosis can be induced and regulated in a similar manner to apoptosis. This has been recently identified as a form of programmed cell death that is different with traditional necrosis and apoptosis [124, 125]. Furthermore, it is a regulated cell death with the morphological characterization of necrosis; which can be pharmacologically inhibited by certain chemical compounds such as necrostatin-1 [126].…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%
“…However, emerging evidence has shown that necrosis can be induced and regulated in a similar manner to apoptosis. This has been recently identified as a form of programmed cell death that is different with traditional necrosis and apoptosis [124, 125]. Furthermore, it is a regulated cell death with the morphological characterization of necrosis; which can be pharmacologically inhibited by certain chemical compounds such as necrostatin-1 [126].…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%
“…Neural cell death plays a key role in this complex pathology and significantly contributes to the final extent of the neural damage (Grossman et al, 2001). In the following hours and days, apoptosis and other forms of programmed cell death (for example necroptosis, autophagic, parthanatos) gradually replace necrosis (Bianchetti et al, 2013;Crowe et al, 1997;Grossman et al, 2001;Kanno et al, 2011;Liu et al, 2014Liu et al, , 1997Lou et al, 1998). During the next days, there is a reduction of the programmed cell death in the impact region (Liu et al, 1997;Lou et al, 1998) followed by a second wave of cell death that affects the white matter away from the impact epicenter (Abe et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports associated the activation of necroptosis to several neurodegenerative conditions (reviewed in Yuan et al, 2019). Inhibition of necroptosis with small molecules or genetic ablation of RIPK1, RIPK3 or MLKL exert neuroprotective effects in models of brain damage, including ischemia (Qu et al, 2016;Yin et al, 2015;Zhang et al, 2016b), traumatic injury (You et al, 2008), viral infections (Bian et al, 2017), in addition to contribute to retinal damage (Dong et al, 2012;Kim et al, 2016;Viringipurampeer et al, 2014) and spinal cord injury (Liu et al, 2015). Recent advances in the field have demonstrated the therapeutic potential of inhibiting necroptosis in several neurodegenerative diseases including amyotrophic lateral sclerosis (ALS) (Ito et al, 2016;Re et al, 2014) multiple sclerosis (MS) (Ofengeim et al, 2015) and Alzheimer's disease (AD) (Caccamo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%